Defining optimal cutoff scores for cognitive impairment using Movement Disorder Society Task Force criteria for mild cognitive impairment in Parkinson's disease. Issue 14 (9th October 2013) - Goldman, Jennifer G.; Holden, Samantha; Bernard, Bryan; Ouyang, Bichun; Goetz, Christopher G.; Stebbins, Glenn T.
ABSTRACT The recently proposed Movement Disorder Society (MDS) Task Force diagnostic criteria for mild cognitive impairment in Parkinson's disease (PD‐MCI) represent a first step toward a uniform definition of PD‐MCI across multiple clinical and research settings. However, several questions regarding specific criteria remain unanswered, including optimal cutoff scores by which to define impairment on neuropsychological tests. Seventy‐six non‐demented PD patients underwent comprehensive neuropsychological assessment and were classified as PD‐MCI or PD with normal cognition (PD‐NC). The concordance of PD‐MCI diagnosis by MDS Task Force Level II criteria (comprehensive assessment), using a range of standard deviation (SD) cutoff scores, was compared with our consensus diagnosis of PD‐MCI or PD‐NC. Sensitivity, specificity, and positive and negative predictive values were examined for each cutoff score. PD‐MCI subtype classification and distribution of cognitive domains impaired were evaluated. Concordance for PD‐MCI diagnosis was greatest for defining impairment on neuropsychological tests using a 2 SD cutoff score below appropriate norms. This cutoff also provided the best discriminatory properties for separating PD‐MCI from PD‐NC compared with other cutoff scores. With the MDS PD‐MCI criteria, multiple domain impairment was more frequent than single domain impairment, with predominant executive function, memory, and visuospatial function deficits. Application of the MDS Task Force PD‐MCI Level II diagnostic criteria demonstrates good sensitivity and specificity at a 2 SD cutoff score. The predominance of multiple domain impairment in PD‐MCI with the Level II criteria suggests not only influences of testing abnormality requirements, but also the widespread nature of cognitive deficits within PD‐MCI. © 2013 International Parkinson and Movement Disorder Society